educational research in the quantitative approach analyzing the presuppositions of Guillermo Briones (Revista Electrónica REDINE, 2018)
The central theme of this essay is the quantitative approach proposed by William Briones in educational research. Therefore, to analyze the relationship between research and pedagogy we must refer and place results of investigations conducted within the social sciences can be incorporated or should be incorporated into the corpus of pedagogy, understood as science synthetic and, possibly, to didactics, understood as the methods and techniques that are used or are suitable for teaching. Despite the boom of the qualitative approach there are investigations requiring its aim and purpose of the hypothetical-deductive approach or simply the triangulation of methods.
Keywords: educational research; quantitative approach; paradigm